Modes of Transmission of Brucellosis in Anbar Governorate, Iraq - Hani Danhash; Rafi Al_Ani; Maher Khaleel (Al-Anbar Medical Journal)
Background: Brucellosis is a common and endemic disease in the Anbar governorate. Besides,  the Brucella microorganism has different ways of transmission. Objective: The study aimed to determine the ways of transmission of Brucella organisms to human beings in the Al-Anbar governorate. Materials and methods: A retrospective study was carried out on patients visiting the two main Ramadi Teaching Hospitals in Ramadi city, Iraq for the diagnosis and treatment of Brucellosis. Patients with blood-culture-positive brucellae were enrolled in the study. The study included the period between February 2002 and March 2005. Data were collected and recorded regarding age, gender, and residence. The possible ways of acquiring the disease were recorded too. These included ingestion of possibly contaminated foods, butchering of animals, meat cutting, keeping animals in homes or nearby their livings, cleaning animal places, caring for, milking of them, aiding in their delivery and if they wear gloves, blowing in the mouth of delivered fetuses, their work, and possible laboratory worker exposure. Results: A total of 312 patients with brucellosis were enrolled in the study. The disease appears to be more common in rural areas (P-value<0.001). More cases were females in all age groups, and it was more common in the age group 31-40. The main mode of transmission is direct or indirect contact with infected domestic animals (P-value<0.001). Lab workers and ingestion of raw milk and unsafe milk products were the least recorded expected risk for infection. Three risky behaviors for acquiring brucellosis were also recognized in this study: milking animals, aiding domestic animals in delivery, and blowing in the mouth of delivered fetuses to promote breathing of the newly delivered animals.   Conclusion: Direct or indirect animal contact was the main way of Brucella transmission in the Al-Anbar governorate.